Preparation and characterization of nanocomposite films and their application in electrochemical sensors to detection of carbohydrates, D-penicillamine and L-tryptophan / Samira Bagheri - Bagheri, Samira (2013)
Nanotechnology has become one of the most important fields in science. The nanoparticles exhibit unique chemical, physical and electronic properties that are different from those of bulk materials, due to their small size and better architecture. Nanoparticles can be used to construct novel sensing devices; in particular electrochemical sensors. Electrochemical detection is highly attractive for the monitoring of glucose, cancer cells, cholesterol and infectious diseases. For the present investigation of my PhD work, the nanomaterials of zinc oxide and anatase titanium dioxide were synthesized by simple and low-cost techniques using gelatin as an organic precursor via the sol–gel method. The analytical and spectroscopic techniques of thermogravimetric analysis, X-ray diffraction, transmission electron microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy and ultraviolet visible spectroscopy were used to characterize the architecture and properties of the synthesized nanomaterials. The result shows that, the metal oxide nanoparticles with high crystallinity can be obtained using this facile method. Gelatin plays a very important role in the formation of zinc oxide and anatase titanium dioxide nanoparticles. Moreover, the composite film was prepared by using the synthesized zinc oxide, multi walled carbon nanotube and polycaprolactone on glassy carbon electrode (ZnO/MWCNT/PCL/GCE). The porous ZnO/MWCNT/PCL film was used as a supporting matrix to immobilize the Co(II) ions. The immobilized Co(II) ion exhibits an excellent electrocatalytic activity to glucose oxidation. The sensor responded linearly to glucose in the concentration of 5.0×10−5 - 6.0×10−3 M with the detection limit of 1.6×10−5 M at 3σ using cyclic voltammetry. In addition, the composite film was prepared by synthesized TiO2-NPs and multi walled carbon nanotube on glassy carbon electrode (TiO2-MWCNT/GCE). The TiO2-MWCNT/GCE responded linearly to L- iv tryptophan in the concentration range of 1.0×10−6-1.5×10−4 M with the detection limit of 5.2×10−7 M at 3σ using amperometric measurement. A nickel (II) into porous polyacrylonitrile- multi walled carbon nanotubes composite modified glassy carbon electrode (Ni/PAN-MWCNT/GCE) was fabricated by simple drop-casting and immersing technique. Ni/PAN-MWCNT/GCE electrode showed good electrocatalytic activity toward the oxidation of carbohydrates (glucose, sucrose, fructose and sorbitol). The electrocatalytic response showed a wide linear range (10–1500 μM, 12–3200 μM, 7–3500 μM and 16–4200 μM for glucose, sucrose, fructose and sorbitol, respectively). At this juncture, I prepared a simple and efficient strategy for the fabrication of nanocrystalline composite films containing chitosan and multi walled carbon nanotube coated on a glassy carbon electrode. The chitosan films are permeable to anionic [Fe(CN)6]3−/4− redox couple. This modified electrode also showed an electrocatalytic effect on the simultaneous determination of D-penicillamine and L-tryptophan. The detection limit of 0.9 μM and 4.0 μM for D- penicillamine and L-tryptophan, respectively, makes this nanocomposite film very suitable for the determination of D-penicillamine and L-tryptophan with good sensitivity and selectivity. In summary, the electrochemical sensors proposed in my PhD work exhibited high sensitivity and selectivity for the continuous monitoring of analytes such as carbohydrates, D-penicillamine and L-tryptophan. The unique nanocomposite-based films proposed in this thesis open new doors to the design and fabrication of high-performance electrochemical sensors.